From environmentalism to transenvironmentalism : the ethnography of an urban protest in modern Istanbul. - Voulvouli, Aimilia (Peter Lang, 2009)
How can the examination of action groups, such as the one discussed in this book, help to initiate a discussion of environmental conflicts as societal conflicts? In this work, which is an ethnographic study of a protest born in Istanbul during the late 1990s, the author suggests that the peculiarities of a protest-group should be viewed as social, political and cultural rather than issue-specific. The book offers a close ethnographic examination of the protest, studying it as a product of the particular character of Turkish public life. It illustrates the particular character of the protest itself as a product of the identities evolving, the activities taking place and the community that these have created amidst the struggle. It is a contribution to the anthropology of collective action and brings together recent studies of the anthropology of social movements, environmentalism and urban settings, with wider literature on social movements, civil society and urban studies and anthropological and sociological studies on Turkey -- Présentation de l'éditeur.